Prediction of Structure and Mechanical Properties of Welded joints Using Analytical Methods. (2016) - Piekarska, Wiesława; Goszczyńska-Króliszewska, Dorota
Abstract: The paper presents analytical methods of the prediction of mechanical properties of welded joints made of S355 steel. Formulas determining so called characteristic temperatures and times for corresponding phase transformations are used in order to build computational CCT diagrams. These empirical relationships are presented in correlation with corresponding cooling rates v 8/5 ( t 8/5 ). Additionally, volume fractions of each phase are determined as a function of cooling rate using analytical models. Mechanical properties of welded joints made of S355 steel are predicted on the basis of obtained phase fractions. Dilatometric research on S355 steel is performed in order to verify obtained analytical results and to evaluate the usefulness of created diagrams of austenite transformation.